Mathematical modelling of water and solute movement in ridged versus flat planting systems. (20th August 2018) - Duncan, S. J.; Daly, K. R.; Sweeney, P.; Roose, T.
Abstract : Summary: We compared water and solute movement between a ridge and furrow geometry and that of flat soil with a mathematical model. We focused on the effects of two physical processes: root water uptake and pond formation on the soil surface. The mathematical model describes the interaction between solute transport, water movement and surface pond depth. Numerical simulations were used to determine how solutes of varying mobility and rates of degradation penetrated into the two soil geometries over a growing season. Both the ridge and furrow or flat soil geometries could reduce solute leaching, but this depended on several factors. Rain immediately after a solute application was a key factor in determining solute penetration into soil. In cases with delayed rain after a solute application, solutes in ridge and furrow geometries collected adjacent to the root system, resulting in reduced solute penetration compared to the flat soil geometry. In contrast, substantial rain immediately after a solute application resulted in ponding where water infiltration acted as the dominant transport mechanism. This resulted in increased solute penetration in the ridge and furrow geometry compared to the flat soil geometry. Highlights: We studied solute movement controlled by ponding in ridge and furrow and flat fields. We found the ridged soil could impede or increase leaching compared to the flat soil. Solute hot‐spots formed in ridge and furrow soil because of root water uptake. Time between solute application and rainfall is a key factor for solute penetration.